Inflammatory Mechanisms of Idiopathic Epiretinal Membrane Formation - Joshi, Malav; Agrawal, Shivi; Christoforidis, John Byron (Mediators of Inflammation, 2013)
The pathogenesis of idiopathic epiretinal membranes (iERMs), a common pathology found in retina clinics, still eludes researchers to date. Ultrastructural studies of iERMs in the past have failed to identify the cells of origin due to the striking morphologic changes of cells involved via transdifferentiation. Thus, immunohistochemical techniques that stain for the cytostructural components of cells have confirmed the importance of glial cells and hyalocytes in iERM formation. The cellular constituents of iERMs are thought to consist of glial cells, fibroblasts, hyalocytes, etc. that, in concert with cytokines and growth factors present in the vitreous, lead to iERM formation. Recently, research has focused on the role of the posterior hyaloid in iERM formation and contraction, particularly the process of anomalous PVD as it relates to iERM formation. Recent advances in proteomics techniques have also elucidated the growth factors and cytokines involved in iERM formation, most notably nerve growth factor, glial cell line-derived growth factor, and transforming growth factor β1.